232k views
0 votes
HELP ME!!!!!!!!!!!!!!!!!!!!!!!!

HELP ME!!!!!!!!!!!!!!!!!!!!!!!!-example-1
User Chenel
by
5.0k points

1 Answer

3 votes

Answer:

The correct option is A

Explanation:

Since (1, 3) are the solutions to the function g(x), then

g(x) = (x – 1)(x – 3) = x² –3x – x + 3 = x² – 4x + 3

We know that f(x) is on the same plane and f(1) = 1.

Let's take g(1) = (1 – 1)(1 – 3) = 0

Therefore, when x = 1; f = 1 and g = 0. Hence

g(1) = f(1) – 1

In order words, g(x) could be f(x) – 1.

The correct option is A

User Chhameed
by
5.3k points